1991
DOI: 10.1016/0035-9203(91)90236-r
|View full text |Cite
|
Sign up to set email alerts
|

A community trial of ivermectin for onchocerciasis in Sierra Leone: adverse reactions after the first five treatment rounds

Abstract: We have studied the adverse reactions reported after ivermectin in 1745 villagers in southern Sierra Leone, allocated at random to receive ivermectin or placebo and treated 'double-blind' with 4 doses at six-monthly intervals. Six months after the fourth dose all eligible villagers received ivermectin regardless of their previous treatment. At the first treatment round more adverse reactions were reported by villagers treated with ivermectin than by those who received placebo. Reactions occurred most often on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…In our study population, the frequency of adverse reactions after ivermectin treatment was much higher (59%) than that reported in other similar studies: De Sole and others found a rate of 9% for adverse reactions to ivermectin in their trial in Ghana, 6 while Whitworth and others reported 28% of the patients with adverse reactions after ivermectin treatment in Sierra Leone. 4 In Liberia, it was found that the rate of adverse reactions was quite low, ranging between 0.6% and 1.3%. 5 One explanation for the much higher occurrence of adverse reactions after ivermectin treatment in Kigoyera parish could be that the community microfilarial load (CMFL) was much lower in Ghana, where only 4.9% of the villages had a CMFL higher than 35 mf/skin snip, while in our eight villages, the CMFL was always greater than 35 mf/skin snip, with an average CMFL of 79 mf/skin snip (range ‫ס‬ 39−128 mf/skin snip).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study population, the frequency of adverse reactions after ivermectin treatment was much higher (59%) than that reported in other similar studies: De Sole and others found a rate of 9% for adverse reactions to ivermectin in their trial in Ghana, 6 while Whitworth and others reported 28% of the patients with adverse reactions after ivermectin treatment in Sierra Leone. 4 In Liberia, it was found that the rate of adverse reactions was quite low, ranging between 0.6% and 1.3%. 5 One explanation for the much higher occurrence of adverse reactions after ivermectin treatment in Kigoyera parish could be that the community microfilarial load (CMFL) was much lower in Ghana, where only 4.9% of the villages had a CMFL higher than 35 mf/skin snip, while in our eight villages, the CMFL was always greater than 35 mf/skin snip, with an average CMFL of 79 mf/skin snip (range ‫ס‬ 39−128 mf/skin snip).…”
Section: Discussionmentioning
confidence: 99%
“…Adverse reactions were generally rare and associated with the microfilaria density in the skin. 4,6,7 All of the studies on adverse effects of ivermectin have been carried out in areas of the Onchocerciasis Control Program (OCP) in west Africa, where Simulium damnosum s.l. is the transmitting vector.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that nearly 20 million people are infected and another 85 million are at risk. Large and diverse populations have been treated with ivermectin in Africa (Burnham, 1993;Chijioke and Okonkwo, 1992;Chippaux et al, 1993;De Sole et al, 1989a,b;Doumbo et al, 1992;Gardon et al, 1997;Ogunba and Gemade, 1992;Pacque et al, 1990Pacque et al, , 1991Whitworth et al, 1991), Polynesia (Cartel et al, 1992), and Latin America (Collins et al, 1992). Typical human doses range from 0.1 to 0.2 mg/kg (FAO/WHO, 1993).…”
Section: Humans: Experience With Ivermectinmentioning
confidence: 97%
“…Though effective, the drugs contribute significantly to severe adverse effects in up to 70% of patients [11,12]. This may be attributed to the action of the drug or the ensuing death of parasites after the administration of the drug.…”
Section: Discussionmentioning
confidence: 99%